Exploring the impact of online graphic narratives in consumer health promotion: A type 2 diabetes study. Issue 4 (2nd October 2021) - Luna-Nevarez, Cuauhtemoc
Abstract: This research explores the use of online graphic narratives (a.k.a. comics) in consumer health promotion. More specifically, the study evaluates the persuasive power of online graphic narratives to communicate type 2 diabetes information, relative to other traditional health communication media such as videos and blogs. A framework including four variables related to narrative processing – narrative transportation, affective response, narrative comprehension, and message comprehension – is proposed. This model compares the effects of the three online media – graphic narrative, video and blog- on consumer persuasion. Overall, the study demonstrates that graphic narratives are more persuasive for health promotion than videos and blogs.